Factors Attributed to Breastfeeding Success in a Tertiary Obstetric Hospital - Felicia V. LeMoine; Caitlin Witt; Shelby Howard; Andrew Chapple; LaKedra Pam; Elizabeth F. Sutton (Mary Ann Liebert, 2022)
Introduction: Increasing breastfeeding rates is a national health objective, however substantial barriers and disparities continue to exist in breastfeeding initiation and continuation. Our study aim is to identify factors associated with birthing persons' breastfeeding ?success? (patients admitted to Labor & Delivery desiring to breastfeed and discharged breastfeeding) and breastfeeding ?failure? (patients admitted to Labor & Delivery desiring to breastfeed and discharged exclusively formula feeding). Materials and Methods: We conducted a retrospective cohort study between July 2015 and June 2016. Patients were asked infant feeding plan intentions (breast, formula, combination) upon admission for delivery. Feeding plan was reassessed at discharge from delivery stay and validated to serve as proxy for feeding status at discharge. Logistic regression was used to identify the population(s) most likely to voice intent to breastfeed and to identify predictors of altered breastfeeding intent at discharge. Results: Between July 2015 and June 2016, 6690 patients met criteria for analysis. Patients reporting intent to breastfeed before delivery were more likely Caucasian (p?<?0.0001), married (p?<?0.001), nulliparous (p?<?0.01), privately insured (p?<?0.0001), educated (p?<?0.0001), and older (p?<?0.01) compared with patients not intending to breastfeed. These characteristics were similar in those who were ?successful breastfeeders,? that is, breastfeeding at discharge. The strongest predictor of breastfeeding at discharge was intent to breastfeed before delivery (p?<?0.0001). African American race was the strongest predictor of nonbreastfeeding intent at admission (p?<?0.0001) and conversion to formula feeding by hospital discharge (p?<?0.001). Conclusion: Intent to breastfeed before delivery was the strongest predictor of breastfeeding at discharge; thus, prenatal breastfeeding education within the at-risk population is crucial to increasing breastfeeding rates.